2012
DOI: 10.1371/journal.pone.0047512
|View full text |Cite
|
Sign up to set email alerts
|

Offspring from Mouse Embryos Developed Using a Simple Incubator-Free Culture System with a Deoxidizing Agent

Abstract: To culture preimplantation embryos in vitro, water-jacketed CO2 incubators are used widely for maintaining an optimal culture environment in terms of gas phase, temperature and humidity. We investigated the possibility of mouse embryo culture in a plastic bag kept at 37°C. Zygotes derived from in vitro fertilization or collected from naturally mated B6D2F1 female mice were put in a drop of medium on a plastic culture dish and then placed in a commercially available plastic bag. When these were placed in an ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…Porcine follicular fluid that was kept at a low temperature for a long time was found to result in reduced oocyte quality . Also, it was reported that high pH in the transportation environment lowered embryo quality . In this study, we mixed HFF with maturation medium in order to prevent evaporation and to improve the HFF environment during transportation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine follicular fluid that was kept at a low temperature for a long time was found to result in reduced oocyte quality . Also, it was reported that high pH in the transportation environment lowered embryo quality . In this study, we mixed HFF with maturation medium in order to prevent evaporation and to improve the HFF environment during transportation.…”
Section: Discussionmentioning
confidence: 99%
“…6 Also, it was reported that high pH in the transportation environment lowered embryo quality. 30 In this study, we mixed HFF with maturation medium in order to prevent evaporation and to improve the HFF environment during transportation. Additional research is required to determine whether HFF should be transported alone or mixed with maturation medium.…”
Section: Discussionmentioning
confidence: 99%
“…Incubator selection is an important decision for the IVF laboratory, as these devices regulate several environmental variables that can impact embryo development. While novel culture approaches may reduce the need for traditional incubators (Blockeel et al, 2009;Hyslop et al, 2012;Itoi et al, 2012;Ranoux and Seibel, 1990;Ranoux et al, 1988;Suzuki et al, 1999;Swain, 2010Swain, , 2011Taymor et al, 1992;Vajta et al, 1997Vajta et al, , 2004Van Blerkom et al, 2013;Varisanga et al, 2000), for the time being they remain a central part of a modern IVF laboratory. Functional aspects of the incubator, such as gas capability and sensor type, as well as temperature control and size/patient capacity need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…On the day of embryo transfer, recipients were anesthetized by intraperitoneal injections of 0.02 mL/g of tribromoethanol. Five to 10 embryos were transferred into each uterine horn [ 4 , 13 ]. Offspring were obtained at 18.5 dpc via Cesarean section, and the body and placental weights were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported the use of a simple incubator-free culture system with a deoxidizing agent [ 4 ]. In this system, most mouse embryos developed into blastocysts in a plastic bag without the need for maintaining humidity, and healthy offspring were obtained.…”
Section: Introductionmentioning
confidence: 99%